(untitled) (Nigerian Journal of Technology, 2015)
In this study, an appropriate head in metre for small hydropower development for the River Ethiope at the source at Umutu was determined. The Dumpy levels and Theodolite method were used to determine the head at the source at Umutu. The results showed that the gross head of the River Ethiope at Umutu is roughly 18.5 m using the Dumpy levels and Theodolite method. However, in every hydraulic structure, there are losses. The head loss was calculated to be 9.3 m thereby placing the net head to be 9.2 m using value from the Dumpy levels. With a head of 9.2 m and a volumetric flow of 31.73 m3/s, the power potential of the River Ethiope was placed at 2.43 MW. It can therefore be concluded that the River Ethiope when fully harnessed could generate electricity to meet part of the power need of the Delta State University, Abraka and the surrounding communities. http://dx.doi.org/10.4314/njt.v35i1.26